Inverse spectral problem for a star graph of Stieltjes strings - Pivovarchik, V. N.; Boyko, O. P. (Methods of Functional Analysis and Topology, 2008)
We solve the inverse spectral problem for a star graph of Stieltjes strings (these are threads bearing a finite number of point masses) with the pendant ends fixed, i.e., we recover the masses and lengths of the intervals between them from the spectra of small transverse vibrations of the graph together with the spectra of the Dirichlet problems on the edges and the total lengths of the edges.